2013
DOI: 10.1007/s11120-013-9793-6
|View full text |Cite
|
Sign up to set email alerts
|

Using site-directed mutagenesis to probe the role of the D2 carotenoid in the secondary electron-transfer pathway of photosystem II

Abstract: Secondary electron transfer in photosystem II (PSII), which occurs when water oxidation is inhibited, involves redox-active carotenoids (Car), as well as chlorophylls (Chl), and cytochrome b559 (Cyt b559), and is believed to play a role in photoprotection. CarD2 may be the initial point of secondary electron transfer because it is the closest cofactor to both P680, the initial oxidant, and to Cyt b559, the terminal secondary electron donor within PSII. In order to characterize the role of CarD2 and to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…The midpoint redox potential of RubA is 1125 mV (Wastl et al, 2000), which is positive enough to allow RubA to keep the acceptor side of PSII oxidized and so prevent the accumulation of singly reduced Q A (due to either inadvertent nonphotochemical reduction or lack of functional Q B ). Another possibility is that reduced RubA might reduce Cyt b 559 within PSII and so act as part of a photoprotective cyclic electron transport pathway involving the oxidation and subsequent rereduction of P680 1 via a pathway involving Q A , RubA, Cyt b 559 , and the Car D2 carotenoid bound to D2 (Shinopoulos et al, 2014). A redox role for RubA is supported by our observation that the DrubA strain is able to proliferate in autotrophic media under continuous illumination but not when exposed to fluctuating light consisting of cycles of 15 min of light and 15 min of dark ( Figure 4A).…”
Section: Discussionmentioning
confidence: 99%
“…The midpoint redox potential of RubA is 1125 mV (Wastl et al, 2000), which is positive enough to allow RubA to keep the acceptor side of PSII oxidized and so prevent the accumulation of singly reduced Q A (due to either inadvertent nonphotochemical reduction or lack of functional Q B ). Another possibility is that reduced RubA might reduce Cyt b 559 within PSII and so act as part of a photoprotective cyclic electron transport pathway involving the oxidation and subsequent rereduction of P680 1 via a pathway involving Q A , RubA, Cyt b 559 , and the Car D2 carotenoid bound to D2 (Shinopoulos et al, 2014). A redox role for RubA is supported by our observation that the DrubA strain is able to proliferate in autotrophic media under continuous illumination but not when exposed to fluctuating light consisting of cycles of 15 min of light and 15 min of dark ( Figure 4A).…”
Section: Discussionmentioning
confidence: 99%
“…Recently it has been shown that one of the two so-called redox active carotenoids, Car D2 , plays a role in photoprotection. Site-directed mutations around the binding pocket of Car D2 in Synechocystis cells revealed the importance of β-carotenes in the initiation of secondary electron transfer processes, which occurs when water oxidation is inhibited ( Shinopoulos et al, 2014 ).…”
Section: The Effect Of Carotenoids On the Architecture And Various Fumentioning
confidence: 99%
“…One can wonder if such success can be in part due to their superior photoprotective mechanisms and if any such traits can be engineered in crop plants to derive yield advantages under particular environmental conditions. It is worth pointing out that the exact molecular mechanism of cyclic electron flow around PSII is not completely understood, but is likely to involve electron transfer via Cyt b-559 and a carotenoid bound to the D2 subunit [ 62 ]. One obvious next step is to express the core subunits of PSII from these strains in a model plant.…”
Section: Improving Photoprotection In a Fluctuating Environmentmentioning
confidence: 99%